Literasi Keuangan Syariah Dan Preferensi Investasi Halal: Studi Grounded Theory Pada Komunitas Muslim Di Kota Makassar - Amin, Andi Mustika (PT Maju Malaqbi Makkarana, 2025)
This study explores the relationship between Islamic financial literacy and halal investment preferences among Muslim communities in Makassar City using a grounded theory approach. Through in-depth interviews with 18 informants from various backgrounds, the research identifies three categories of Islamic financial literacy levels: Basic Literacy (7 informants), Intermediate Literacy (8 informants), and Advanced Literacy (3 informants). The findings reveal a strong correlation between literacy levels and investment diversification, showing a paradigmatic transformation from